Determinan Ketahanan Pangan Rumahtangga di Kabupaten Tulang Bawang Selama Pandemi Covid-19 - Afifah, Nurul; Prasetyaningtyas, Woro Ayu (Hasanuddin University, 2024)
Food security is one of the goals that must be maintained during the Covid-19 pandemic. However, the current economic conditions have led to a reduction in people's income due to a decrease in productive business activities, resulting in an increase in unemployment and poverty. This is quite worrying for the government in the event of a food crisis in the future. Tulang Bawang Regency is one of the areas that has felt the impact of the Covid-19 pandemic. Therefore, this study aims to determine the description of food security in Tulang Bawang Regency and the variables that influence it. The results of the multinomial logistic regression analysis found that a small number of household members, a high education of the head of the household, as well as a non-poor poverty condition will increase the chances of the household being food secure.